Commonalities for comorbidity: Overlapping features of the endocannabinoid system in depression and epilepsy - Epps, S. Alisha (Frontiers in Psychiatry, 2022)
A wealth of clinical and pre-clinical data supports a bidirectional comorbidity between depression and epilepsy. This suggests commonalities in underlying mechanisms that may serve as targets for more effective treatment strategies. Unfortunately, many patients with this comorbidity are highly refractory to current treatment strategies, while others experience a worsening of one arm of the comorbidity when treating the other arm. This highlights the need for novel pharmaceutical targets that may provide safe and effective relief for both depression and epilepsy symptoms. The endocannabinoid system (ECS) of the brain has become an area of intense interest for possible roles in depression and epilepsy. Several existing literature reviews have provided in-depth analysis of the involvement of various aspects of the ECS in depression or epilepsy separately, while others have addressed the effectiveness of different treatment strategies targeting the ECS in either condition individually. However, there is not currently a review that considers the ECS when both conditions are comorbid. This mini-review will address areas of common overlap between the ECS in depression and in epilepsy, such as commonalities in endocannabinoids themselves, their receptors, and degradative enzymes. These areas of overlap will be discussed alongside their implications for treatment of this challenging comorbidity.